Strange bedfellows? Consumer culture and the moral order in the post-socialist world – An afterword. (May 2020) - Shevchenko, Olga
Critiques of consumption frequently assume moral undertones, with the effect of obscuring the moral foundations underlying consumer practices themselves. The articles in this collection offer compelling and ethnographically rich evidence of the moral tensions that inform consumer preferences in post-socialist Europe. Consumer behaviors and discourses have historically played an important role in the region, determining grounds for social inclusion under socialism as much as under capitalism. This makes post-socialist settings particularly rich sites for ethnographic studies of the intersection between consumer culture and the moral order, as it allows us to trace how the criteria for full social membership – a chance to be seen, heard, and treated with respect – relate to consumption under different economic and political regimes.